2021
DOI: 10.1007/s40789-021-00438-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical characteristics of composite briquette from coal and pretreated wood fines

Abstract: Melina wood torrefied at 260 °C for 60 min was agglomerated with lean grade coal fines into composite briquettes using pitch as binder. Torrefied biomass (3%–20%) and coal fines (80%–97%) were blended together to produce the composite briquettes under a hydraulic press (28 MPa). The briquettes were cured at 300 °C. Density, water resistance, drop to fracture, impact resistance, and cold crushing strength were evaluated for the composite briquettes. The proximate, ultimate, and calorific value analyses were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
4
23
2
Order By: Relevance
“…This is expected as unbounded moisture loss, light volatiles evolution and reactive drying takes placed at 300 24 . The density of the briquettes produced in this study is a little higher than our previous studies 1 , 2 . This is because of the addition of bentonite, which is denser than the binders (molasses and pitch) used in those studies.…”
Section: Resultscontrasting
confidence: 71%
See 4 more Smart Citations
“…This is expected as unbounded moisture loss, light volatiles evolution and reactive drying takes placed at 300 24 . The density of the briquettes produced in this study is a little higher than our previous studies 1 , 2 . This is because of the addition of bentonite, which is denser than the binders (molasses and pitch) used in those studies.…”
Section: Resultscontrasting
confidence: 71%
“…Further drying was done in an oven at 105 for 30 min to eliminate unbounded moisture as previously described by Adeleke et al 1 . The proximate, ultimate and calorific value (HHV) as reported by Adeleke et al 2 are shown in Table 1 . The details of torrefaction of melina has also been reported by Odusote et al 7 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations